The Behaviour of the Financing Decision of the Russian Listed Companies - Rustamov, Bezhan (Springer Science and Business Media B.V., 2019)
This study investigates the presence of the market timing theory in the case of Russian firms for the periods of 1992–2013 and 2003–2013 using the two-step system GMM panel estimators (Arellano and Bover in J Econ 68:29–51, 1995; Blundell and Bond in Econ Rev 19:321–340, 1998) and the Fama and MacBeth two-step procedure (Fama and MacBeth in J Polit Econ, 607–636, 1973). The main aim of the study is to observe the effect of the market timing on the capital structure by controlling the key determinants of firms’ financing decision. The two-step system GMM results imply that the calculated historical market to book measure has a negative coefficient and it indicates the presence of the market timing on capital structure. The persistence effect of market timing is confirmed by employing the Fama and MacBeth two-step procedure (Fama and MacBeth in J Polit Econ, 607–636, 1973). The result of the test reveals that even in 10 years the 55% persistency of the initial effect of the market timing on the capital structure for the matured listed Russian firms is observed. © 2019, Springer Nature Switzerland AG.
4th International Conference on Banking and Finance Perspectives, ICBFP 2019 -- 2019-05-02 through 2019-05-03 -- Famagusta -- 273729
Keywords: Capital structure; GMM; Market timing; Tax